Pozycja prawnoustrojowa Komisji do spraw Wymiaru Sprawiedliwości Malty - Kuźnicka-Błaszkowska, Dominika (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
The Commission for the Administration of Justice of Malta is an advisory and control body of the judiciary which, in accordance with the Constitution of Malta, safeguards the independence of judges. Despite the reform of its system and scope of competence in recent years, social activists are still demanding changes in the way it functions. The main allegations relate primarily to the too strong position of the executive representatives in its work, the lack of openness of the Commission, as well as nepotism and corruption in the judicial community.
Keywords: justice system; Malta; position of judges